SEJARAH PERKEMBANGAN MUALAF DI SABAH, PERANAN DAN SUMBANGAN USIA ( UNITED SABAH ISLAMIC ASSOCIATION) - Sintang, Suraya (Journal of Al-Tamaddun, 2005)
The involvement of USIA in the Islamic movement is considered as a vital historical event inseparable from the whole process of Islamic development in Sabah. As the pioneer of the dakwah institution in Sabah, USIA organized the Islamization programme with the focus on the activity of multitude conversion among the target groups of Sabah?s natives whom live in the interior areas. These areas were the main residence of animist people who had not yet adhered to either Islam or Christianity. The mission of multitude conversion launched in 1970s was conducted for a few reasons. Among the factors contributed to the mission were the disapproval of recongnizing Islam as an official religion in Sabah, the competitiveness between the numbers of new Muslim converts and Christian adherents from among the Sabah?s natives, the dilemma of practicing Islamic creeds and Syariah law and the challenge from the Christian missionary. Therefore, this paper initiates to look back at the history of multitude conversion and discuss the latest development of converters. The discussion will be focused on the contribution of USIA in conducting such Islamic programme. The contributions could be stated such as the formation of The Sabah Islamic Council (MAIS) which brought to the approval of recognizing Islam as an official religion in Sabah. Moreover, the contribution of USIA also led to the emergence of new Muslim converts and their villages, the construction of new religious schools and worship places and also the birth of literate-religious people among the Sabah?s natives.